(untitled) (Research, Society and Development, 2021)
Introduction: Submandibular tracheal intubation is a technique that can be applied in Oral and Maxillofacial Surgery and Traumatology, as well as other surgical specialties. Its main advantages are helping in the surgical manipulation of the middle facial skeleton and jaw and allowing the intraoperative control of dental occlusion. The technique is an alternative to elective tracheostomy. Objective and case report: The article presents the treatment of an adult patient, with sequelae of multiple fractures in the face due to a car accident, with endotracheal intubation using submandibular approach. Final considerations: In large surgical manipulations of the face, the submandibular approach for tracheal intubation allows a faster, facilitated anatomical access with a lower risk of damage to adjacent structures when compared to other pathways. It also guarantees excellent cervical mobility, the possibility of wide manipulation and the use of occlusion as a guide for surgical intervention.